Are We Faced with Two Human Species? - Mladen Davidovic (The Scientific World Journal)
Problems could be found in the fact that we very often look for one deciding, definitive reason for the process of aging. It is a sort of search for a big discovery, like a fountain of youth or such. More and more authors are trying to explain the unknowns in the understanding of these observations about aging by adding the statement that there are two subgroups in the general population. This acknowledgment of two subpopulations explains why there are numerous cases that cannot be explained, defined, or fitted in basic observations about caloric restrictions and the delay of reproduction. The identification of those two groups would allow us to find more realistic results in studies and therefore a more efficient therapy of certain diseases. This hypothesis does not contradict theories of aging that we have accepted (at least not the majority of accepted theories), and this hypothesis also does not contradict the fact that there is a large interindividual variability. This hypothesis doubts, and claims there are exceptions to, the starting assumption of geriatrics and gerontology that: parallel to the aging process the functions of all organs and organ systems lessen.